PENEGAKAN HUKUM LINGKUNGAN TERKAIT DENGAN PENCEMARAN UDARA DI KOTA DENPASAR SETELAH KELUARNYA PERATURAN GUBERNUR BALI NOMOR 8 TAHUN 2007 SERTA UPAYA PENANGGULANGANNYA - Trisnajaya, Tude; Dewi Kasih, Desak Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013, 2013)
As the center of government, education and commerce, Denpasar City are required to keep developing to fulfill the facilities and infrastructures. Along with that, the environmental issues that we are dealing with are getting complex. Activities such as agriculture, tourism, industry, trade and transportation affect the existing resources, such as the ambient air pollution in certain areas or environments. The implementation of environmental quality standard and criteria for environmental damage under the Regulation of Governor Bali Number 8 of 2007 is able to be used as to enforce the environmental law to maintain the quality of ambient air in Denpasar.
Keywords: Quality, Ambient Air, Environment, Ambient Air Quality